Weichselian stratigraphy and glaciotectonic deformation along the lower Pechora River, Arctic Russia. - Henriksen, Mona; Mangerud, Jan; Maslenikova, Olga; Matiouchkov, Alexei; Tveranger, Jan (PANGAEA, 2001)
A large section near the village of Hongurei on the Pechora River, ca. 100 km inland from the Barents Sea coast, reveals the following stratigraphic record of the last glaciation: The lowest units are lacustrine silt overlain by fluvial sand. These two units are repeated by glaciotectonic upthrusting from the NW. On top of this stacked succession is a till where fabric measurements reflect ice movement from the NE. Above the till is a partly laminated glaciolacustrine clay, probably deposited during the deglaciation of the site. We interpret the two ice flow directions to reflect a single ice advance. The Hongurei site is situated on the eastern rim of a marginal lobe of the Markhida moraine complex. Upthrusting from the NW is interpreted as lateral thrusting along the eastern flank of the NE-SW-oriented lobe, whereas the NE till fabric shows flow direction of the same glacier moving across the site. A maximum age for the last ice advance is given by optical stimulated luminescence (OSL) dates of the fluvial sand below the till, dated to 85 ka at this site, but about 60 ka at other sites along the lower Pechora area.
Weichselian stratigraphy of sediments from the lower Pechora River
Keywords: agedetermination; facieslogs; Hon1050m; Hon200m; Hon520m; Hon610m; Hon640-660m; Hon790-830m; Hon890m; Hongurei; Markhida; OUTCROP; Outcrop sample; Pechora1994; Pechora1996; Quaternary Environment of the Eurasian North; QUEEN; QUEEN_Exped; Sampling on land; Sula; Sula21; Sula22; Urdyuzhskaya_Viska; Vastiansky_Kon